L-lysine Functionalized Mesoporous Silica Hybrid Nanoparticles for pH-Responsive Delivery of Curcumin - Madhappan Santhamoorthy; Vanaraj Ramkumar; Kokila Thirupathi; Lalitha Gnanasekaran; Vanitha Karuppannan; Thi Tuong Vy Phan; Seong-Cheol Kim (MDPI AG, 2023)
Stimuli-responsive controlled drug delivery systems have attracted the attention of researchers in recent decades due to their potential application in developing efficient drug carriers that are responsive to applied stimuli triggers. In this work, we present the synthesis of L-lysine (an amino acid that combines both amine and carboxylic acid groups in a single unit) modified mesoporous silica nanoparticles (MS@Lys NPs) for the delivery of the anticancer bioactive agent (curcumin, Cur) to cancer cells. To begin, mesoporous silica hybrid nanoparticles (MS@GPTS NPs) with 3-glycidoxypropyl trimethoxy silane (GPTS) were synthesized. The L-lysine groups were then functionalized onto the mesopore channel surfaces of the MS@GPTS NPs through a ring-opening reaction between the epoxy groups of the GPTS and the amine groups of the L-lysine units. Several instrumental techniques were used to examine the structural properties of the prepared L-lysine-modified mesoporous silica nanoparticles (MS@Lys NPs). The drug loading and pH-responsive drug delivery behavior of MS@Lys NPs were studied at different pH levels (pH 7.4, 6.5, and 4.0) using curcumin (Cur) as a model anticancer bioactive agent. The MS@Lys NPs' in vitro cytocompatibility and cell uptake behavior were also examined using MDA-MB-231 cells. The experimental results imply that MS@Lys NPs might be used in cancer therapy as pH-responsive drug delivery applications.